Survey on chemical, physical, and thermal prediction behaviors for sequential chemical treatments used to obtain cellulose from Imperata Brasiliensis - de Carvalho Benini, Kelly Cristina Coelho [UNESP]; Ornaghi, Heitor L. [UNESP]; Pereira, Paulo Henrique Fernandes [UNESP]; Maschio, Leandro José; Voorwald, Herman Jacobus Cornelis [UNESP]; Cioffi, Maria Odila Hilário [UNESP] (Springer Nature, 2020)
The effects of chemical treatment sequences on the chemical, physical, and mainly the thermal properties of Imperata Brasiliensis grass in the process used to obtain cellulose fibers were analyzed. The thermal properties were extensively investigated by a thermogravimetric analysis, and a thermal behavior prediction was carried out using kinetic parameters and simulation. Thermal simulations using statistical tools enable thermal predictions for any material under different conditions. However, they are currently not widely reported in the literature for untreated and treated natural fibers. We used an alkaline treatment and alkaline treatment followed by one, two, or three bleaching steps with hydrogen peroxide (H2O2) (24% v/v). After each chemical treatment, changes in chemical composition due to the removal of amorphous constituents were observed and confirmed by the analysis of properties such as coloration, density, porosity, crystallinity, and thermal decomposition. The alkaline treatment followed by one step of bleaching was the most effective and viable chemical treatment sequence to obtain cellulose. The changes in coloration from dark brown to light yellow were accompanied by increases in real density (65%), crystallinity (69%), and thermal stability (27.4%) upon one step of bleaching. In general, the subsequent bleaching steps provided similar values. The predicted thermal degradation profiles were compared with experimental data in order to validate the proposed degradation mechanisms and models. The obtained kinetic parameters adequately described the mass loss histories of the studied natural fibers, even when extremely simplified kinetic schemes were used. The degradation mechanisms consisted of diffusion followed by autocatalytic reactions for all studied fibers.
Keywords: Chemical treatment; Imperata Brasiliensis; Thermal simulation